2019
DOI: 10.1017/ice.2019.199
|View full text |Cite
|
Sign up to set email alerts
|

Reduced isolation room turnover time using Lean methodology

Abstract: Objective:To prevent environmental transmission of pathogens, hospital rooms housing patients on transmission-based precautions are cleaned extensively and disinfected with ultraviolet (UV) light. To do so consistently requires time and coordination, and these procedures must avoid patient flow delays and associated safety risks. We sought to improve room turnover efficiency to allow for UV disinfection.Design:A 60-day quality improvement and implementation project.Setting:A quaternary academic pediatric refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
(48 reference statements)
0
19
0
1
Order By: Relevance
“…An inefficient preoperative department can delay the start of surgery and impact the patient flow throughout the day [ 112 ], which can affect other outcomes, such as TOT and TAT, which are important performance parameters for the perioperative process. We found that LH led to reductions of TOT in six studies, the largest being a 50% reduction [ 104 ]. In contrast, two papers reported no significant changes in TOT, but other benefits, such as reductions from patient in room to procedure starting or OTS [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inefficient preoperative department can delay the start of surgery and impact the patient flow throughout the day [ 112 ], which can affect other outcomes, such as TOT and TAT, which are important performance parameters for the perioperative process. We found that LH led to reductions of TOT in six studies, the largest being a 50% reduction [ 104 ]. In contrast, two papers reported no significant changes in TOT, but other benefits, such as reductions from patient in room to procedure starting or OTS [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This importance has been pointed out by other studies [134,[161][162][163][164]. Other common tools include standard work, i.e., a concept whereby each work activity is precisely described with a specific cycle time, task sequence, and other steps involved within the process [95], and is considered a prerequisite for flow [10]; the 5'S program, which is used to eliminate clutter [165] and enhance the standardization of stock, as well as to systematically organize the unit and streamline the documentation processes [97]; cause and effect analyses, which are used to map the possible causes of a problem into categories [90,166]; and Kaizen, which is a philosophy of continuous incremental improvement over time and space [29,99,104]. These findings are similar with those reported in previous studies [44,62,161], and sustain the assertion that most LH interventions focus more on tools related to assessment and improvement and less on processes-monitoring tools.…”
Section: Lean Healthcarementioning
confidence: 99%
“…Our short- and long-term success was largely due to our team’s commitment to Lean principles and methods. Historically, Lean’s impact in healthcare has been in short-term gains, 7–10 whereas long-term improvement and sustainability have been less clear. 11,12 This observation may be because, in most healthcare systems, an individual “siloed” focus is the standard and conflicts with Lean’s goal to involve all operators in intervention design and execution, independent of hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Application of improvement science principles has improved the consistency of cleaning of hospital-room surfaces and the efficiency of ultraviolet light disinfection. 32,[34][35][36]…”
Section: Environmental Cleaningmentioning
confidence: 99%